Neolithic settlement and paleopedological changes during the Middle Holocene in northern Sardinia (Italy) - Marras, Gian Battista; Boschian, Giovanni (Frontiers in Environmental Archaeology, 2023)
Sardinia is the second biggest island in the Mediterranean region and has been intensely settled since the Middle Holocene (c.7750 cal BP). Despite a large number of Neolithic archaeological sites known, very little is known about human-environmental interactions, including land use and domestic activities associated with the emergence and expansion of Neolithic settlement (c. 7750 and 5500 years cal BP). New geoarchaeological analyses of buried soils and archaeological sequences exposed at the site of Contraguda, northern Sardinia, reveal the earliest record of environmental change associated with anthropic activities during the Middle Holocene. Soil micromorphology detected the presence of pedofeatures originating from agricultural and animal herding activities in both archaeological deposits and buried soils (Entisol and Vertisol). Furthermore, sediment fabric and textural pedofeatures also allowed us to show that household maintenance waste was dumped into pit structures. Our results provide the first geoarchaeological evidence of human impact on soil development within the island during the Middle Holocene and give new insight into the Middle Neolithic (c. 6500 – 6000 cal BP) domestic behaviour and land use activities. These findings have significant implications for understanding the island’s pedological history and shed new light on the settlement organisation of the Neolithic farming communities and their impacts on the palaeoenvironment of Sardinia.